Do Key Audit Matters Signal Corporate Bankruptcy? - Mahmoud Elmarzouky; Khaled Hussainey; Tarek Abdelfattah (Journal of Accounting and Management Information Systems (JAMIS), 2022)
Research Question - This paper aims to answer whether the Key Audit Matters (KAMs) Signaling Corporate Bankruptcy and investigate auditor responsibility versus the lack of auditing standards, and examine whether the disclosure of the KAMs by independent auditors enhances the prediction of corporate bankruptcy and the extent to which the KAMs reduce the information asymmetry between firm managers and shareholders. Motivation - We analyse the risk topics in the annual reports, then the KAMs highlighted by the auditor and then the KAMs are disclosed by adopting a case study approach. Data - We use a single descriptive case study approach and read the relative academic and professional literature to explore the KAMs included in the auditors' reports before the Thomas Cook Group Plc bankruptcy. Findings - We find no significant predicting power of KAMs disclosed by Ernst & Young (EY) on Thomas Cook's annual reports. We found that the auditor is not responsible for indicating financial failure. Contribution - We suggest that the regulators and the accounting boards adopt more restrictive standards and improve the International Standards on Auditing (ISA) 701. Furthermore, attention should be focused on the reliability of KAMs specified in ISA 701. We conclude that the KAMs are ineffective in disclosing bankruptcy risk. Our paper concludes that the current auditing standards should be more instructive in preventing corporate bankruptcy. We contribute to the literature in a unique and core research area not researched previously.
Keywords: M41; 650; Key Audit Matters; Extended audit report; Risk disclosure; Bankruptcy